A histomorphological pattern of gallbladder lesions in a tertiary hospital in Southwestern Nigeria: a retrospective descriptive study (2021)
BACKGROUND: The gallbladder is one of the most common specimens encountered in the surgical pathology laboratory, and gallstone related diseases are among the most common medical problems requiring surgical intervention. This study's objective was to determine the histomorphological patterns and frequency of gall bladder lesions from cholecystectomy specimens received in our institution for over twenty years. METHODS: We carried out a retrospective review of all cholecystectomy specimens received at the pathology department for 20 years from January 1999 to December 2018. The specimens were obtained from within and outside the hospital facility. The demographic data, clinical details, and histological diagnosis were retrieved from the departmental records and were analyzed with SPSS version 23. RESULTS: A total of 211 cholecystectomy specimens were received during the study period. Patients’ age ranged from 14 to 84 years, with a mean age of 47.6 ± 0.899 years. There was a female preponderance with male to female ratio of 43:168 (1:3.9). Surgery for gallbladder disease was most commonly performed in the age range of 41-50 years. Out of the 211 specimens, 153 (72.5%) had calculi and 58 (27.5%) were acalculous. Chronic calculous cholecystitis was the most common histopathological diagnosis (65.4%). Others were chronic acalculous cholecystitis (18.0%), acute on chronic acalculous cholecystitis (2.4%), adenocarcinoma (3.3%), metastatic adenocarcinoma (0.1%), adenocarcinoma with chronic calculous cholecystitis (0.5%), klatskin tumour (0.5%), and normal gallbladders (1.9%). CONCLUSION: This study revealed that the commonest indication for cholecystectomy in our hospital was gall stone disease. Malignancy of the gallbladder is uncommon in our center.